2003
DOI: 10.22358/jafs/67666/2003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplemental vitamin E and dietary rape seed oil level on broiler performance, meat and fat quality

Abstract: The effect of increasing dietary vitamin E levels in diets containing animal fat and rape seed oil on the performance, α-tocopherol content of tissues, meat and fat quality, and health of broiler chickens was investigated. A total of 360 Ross broiler chickens were fed diets with the addition of different levels of vitamin E (5, 20 and 50 mg • kg-1) during the starter (0-17 days of age) and grower (18-42 days of age) periods. Grower diets were supplemented with animal fat with or without 10 or 20% rape seed oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
2
1
1
Order By: Relevance
“…In the group with additional supplementation of both vitamin E and Se, FCR was also significantly worse than in the remaining groups. These findings are in opposition to those of many authors, who reported that the modification of the dietary n-6/n-3 PUFA ratio with the use of plant oils and/or supplementation of diets with higher levels of vitamin E or vitamin E and Se is usually without consequences (Cortinas et al, 2004;Kim et al, 2010;Qi et al, 2010) or has positive effects on bird performance (Młodkowski et al, 2003;Koreleski and Świątkiewicz, 2006).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In the group with additional supplementation of both vitamin E and Se, FCR was also significantly worse than in the remaining groups. These findings are in opposition to those of many authors, who reported that the modification of the dietary n-6/n-3 PUFA ratio with the use of plant oils and/or supplementation of diets with higher levels of vitamin E or vitamin E and Se is usually without consequences (Cortinas et al, 2004;Kim et al, 2010;Qi et al, 2010) or has positive effects on bird performance (Młodkowski et al, 2003;Koreleski and Świątkiewicz, 2006).…”
Section: Discussioncontrasting
confidence: 96%
“…Similar results were presented by Młodkowski et al (2003) and Koreleski and Świątkiewicz (2006). Feeding the diet supplemented with a higher level of vitamin E combined with excessive Se level had no effect on the α-tocopherol concentration in meat, similarly as in the study by Taulescu et al (2011).…”
Section: Discussionsupporting
confidence: 87%
“…The increases in vitamin E content in breast meat from increased amounts of α-tocopherol added to the diet are in agreement with the results of Młodkowski et al (2003) and Carreras et al (2004). The vitamin E concentration increased in a dose-dependent manner, but the contribution of EPA and DHA in lipids was not affected.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier experiments with growing pigs with either addition of animal fat or rapeseed oil showed that digestible fat improved the efficiency of utilisation of metabolisable energy (ME) substantially (Just 1982;Jørgensen et al 1996a). However, fat inclusion in broiler diets affects carcass fat quality, because dietary fatty acids can be incorporated directly into body fat (Olomu and Baracos 1991;Scaife et al 1994;Engberg et al 1996;Jakobsen 1999;Mlodkowski et al 2003). Furthermore, the efficiency of utilisation of ME is improved, since the energetic costs of intestinal breakdown, and transport to and synthesis within the liver are avoided (Krogdahl 1985).…”
Section: Introductionmentioning
confidence: 99%